Effect of LHP Nanosilica on Sandstone Wettability and Oil Recovery by Imbibition in Crude Oils with Different API - Jumiati, Wiwiek; Hani, Berkah; Yanti, Widia; Sutresno, Wahyu; Wihdany, Falza Izza; Ghaziyah, Hawa Syuraih; Herlambang, Karyanto; Celli, Agli Tori; Wibowo, Gilang Saputra (Testing Center for Oil and Gas LEMIGAS, 2026)
This study investigates the influence of lipophobic–hydrophilic polysilicon (LHP) nanosilica on wettability alteration and oil recovery performance through spontaneous imbibition in initially neutral-wet sandstone. The novelty of this study lies in its systematic comparative framework using two crude oils with distinct API gravities and SARA compositions to evaluate the role of fluid–rock interactions in depth. Two crude oils with different API gravities were selected to evaluate the role of oil composition in fluid–rock interactions. Crude oil properties were characterized using SARA analysis, while imbibition tests were conducted using 5000 ppm brine and nanosilica dispersions at controlled concentrations. Wettability Index (WI) was determined using the Amott cell method, and Oil Recovery Factor (ORF) was calculated from produced oil volume. Results indicate that LHP nanosilica consistently shifts rock wettability toward more water-wet conditions. The lighter crude oil exhibits a stronger wettability response and higher recovery improvement than the heavier oil. A positive correlation between WI and ORF confirms wettability alteration as the dominant enhanced oil recovery mechanism. These findings provide a significant contribution by establishing crude oil characteristics as a key controlling factor in nanofluid EOR design, which is crucial for field applications with complex fluid variations.